Construction prosodique de la violence chez Métal Urbain : l’exemple du 45 tours Paris Maquis (1977) - Olivier Migliore (Criminocorpus)
Métal Urbain is a French punk band close to anarchist movements formed in 1976. It released a first SP in 1977 under the English label Rough Trade. This one contains two titles, « Paris Maquis » – name given to the SP – and « Clé de contact ». In both pieces, the singer makes extremely radical remarks fundamentally challenging the republicans good manners and order. To this radicality of the discourse is added an instrumental play, phonatory specificities, and a musical prosody that contribute to constructing a feeling of violence in keeping with the ideological radicalism of Métal Urbain, specificities that we will study using a computer-assisted analysis method of the musical prosody.